Cross-talk between miR-471-5p and autophagy component proteins regulates LC3-associated phagocytosis (LAP) of apoptotic germ cells - Subbarayalu Panneerdoss (Nature Portfolio, 2017)
Although phagocytic clearance of apoptotic germ cells by Sertoli cells is essential for spermatogenesis, little of the mechanism is known. Here the authors show that Sertoli cells employ LC3-associated phagocytosis (LAP) by recruiting autophagy member proteins to clear apoptotic germ cells.